EFFECT OF FEEDING SOME ADDITIVES ON YIELD, TOTAL , SOLIDS AND SOLIDS -NOT - FAT CONTENT OF COWS MILLK - C.T. Sathian (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
The effect of feeding acetic acid (200 ml/d), sodium biearbonate (1.5% of concentrate feed), potassium carbonate (1.2% of the concentrate feed) and magnesium oxide (0.8 % of the concentrate feed) on yield, total solids (TS) and solids-not-fat (SNF) contents of cows milk was sutdied. Feeding was done for 25 days. Potassium carbonate feeding increased TS % significantly from 12.26 to 12.68 while there was a significant reduction in milk yield (11.71 kg/day). Nuns of the additives produced significant changes in SNF%. Feed consumption by the animals was not affected by feeding any of the additives.